Drip Irrigation Technology for Watermelon Crops with IoT-Based Solar Panels for Efficient Use of Energy Resources - Azahra, Maulida; Styawati, Styawati (IC-ITECHS, 2024)
Water scarcity and energy inefficiency are major challenges in modern agriculture, particularly for water-intensive crops like watermelon. This study aims to develop a sustainable solution by integrating drip irrigation technology with IoT-based solar panels to optimize water and energy use. The purpose of this research is to design and test a system that uses renewable solar energy and IoT sensors to monitor soil moisture and control irrigation automatically, providing an efficient and environmentally friendly solution for watermelon farming. The methodology involves the development of a prototype system powered by solar panels and equipped with IoT sensors for real-time data collection and system management. The findings demonstrate that the solar-powered IoT drip irrigation system significantly reduces water consumption and energy costs compared to conventional irrigation methods, ensuring efficient water use while operating off-grid. The practical implications of this study suggest that this integrated system can be scaled for large-scale farming operations, improving crop yields and contributing to sustainable agricultural practices. The results highlight the potential of combining renewable energy, IoT, and modern irrigation techniques as a viable solution to address global challenges of water conservation, energy efficiency, and sustainable farming.